Corrosion. Volume 1, Metal/environment reactions - Shreir, L. L.; Burstein, G. T.; Jarman, R. A. (Oxford ; Boston : Butterworth-Heinemann, 1994)
This book provides an encyclopedic coverage of corrosion science and technology. It is a reference work embracing topics including high-temperature and aqueous corrosion and their control.
Principles of corrosion and oxidation -- Environments -- Ferrous metals and alloys -- Non-ferrous metals and alloys -- Rarer metals -- The noble metals -- High-temperature corrosion -- Effect of mechanical factors on corrosion.
Title from title screen (viewed Aug. 25, 2009).
Includes bibliographical references and index.
Available through Referex Materials & Mechanical on Engineering Village.
Keywords: Corrosion and anti-corrosives.; Electronic books